Port infrastructure, urbanization and extractivism: a study of the social production of space in the Rosario region, Argentina (1995-2021) (Desarrollo, Estado y Espacio, 2023)
In a global system marked by increasingly unequal economic and ecological exchanges, Latin America is becoming a financial valuation platform specialized in the extraction of commodities. Extractivism, driven by the super-cycle of raw materials, has led to numerous and varied material and immaterial transformations on the subcontinent. This, through an enduring unequal relationship and tied up by extensive and armored global value chains, continues to feed the growth of planetary urbanization led by a small group of transnational oligopolies (Brenner, 2019). The objective of this article is to explore the continuity of the extractive process transversal to the urban-regional space and to analyze the interactions between urbanization and the port infrastructure of the Rosario region over the last quarter of a century (1995-2022). We have followed the theoretical-methodological proposals of Martin Arboleda (2020) and Carlos Brandão (2017, 2022). Based on these contributions, we have analyzed the extractivist production process and observed the interdependencies, interrelationships and intersections among actors in the urban-regional space produced by the dominant extractive process.
Keywords: Port infrastructure; urbanization; extractivism; social production of space; extractive spatial transversality